Rancang Bangun Sistem Informasi Berbasis Website Sebagai Media Informasi dan Pengarsipan Dokumen pada Forum Anak Kecamatan Tigaraksa (FATIGAS) - Sultan Alif Syahbana; Sulthan Ghatfan Naufal Abbad; Bima Pratama Setiawan (CV. Shofanah Media Berkah, 2026)
Data management and information dissemination in community organizations in the digital era often face efficiency barriers when relying on conventional methods or non-integrated third-party platforms. The Tigaraksa District Children's Forum (FATIGAS), as a highly active child aspiration platform, faces significant challenges in publishing organizational profiles and archiving legality documents, such as Decrees (SK), which are currently still based on a